Peningkatan Kualitas Manajemen Keuangan UMKM Melalui Literasi Keuangan dan Go-Digital - Segarawasesa, Fajar Satriya; Hafni, Diska Arliena (Rahmatan Lil 'Alamin Journal of Community Services, 2025)
This activity was carried out to address the challenges faced by micro, small, and medium enterprises (MSMEs) at UKM Aliya, Dusun Gamol Balecatur, particularly the limited understanding of financial management. The main issue identified was the absence of separation between personal and business finances, which made it difficult for business owners to assess their financial performance objectively. To enhance financial management capabilities, a financial literacy training program was conducted, covering basic financial management concepts and the practical use of an Android-based accounting application for preparing financial statements. The application was chosen for its accessibility and user-friendly interface, making it suitable for small business operators. The training was implemented through educational sessions and direct mentoring, allowing participants to learn interactively. Based on the evaluation results, participants showed positive responses and improved understanding, although some still required continued guidance due to the limited mentoring time.